Persian leopard predation patterns and kill rates in the Iran–Turkmenistan borderland - Farhadinia, M; Johnson, P; Hunter, L; Macdonald, D (Oxford University Press, 2018)
Describing predation patterns and especially estimating kill and consumption rates is essential for understanding the functional responses of predators. An understanding of the carrying capacity of the landscape, based on prey availability, also helps to formulate recovery plans for persecuted species. We studied the feeding behavior of the Persian leopard (Panthera pardus saxicolor) in Tandoureh National Park (355 km2) in northeastern Iran, near the Turkmenistan border. Between September 2014 and May 2017, we collared and monitored 6 adult leopards (5 males and 1 female) using GPS-satellite Iridium collars. We investigated 310 clusters of fixes as likely to be kill sites. In total, 130 kills were identified to species, suggesting a mean kill rate of approximately 3.3 ± 0.3 (SE) kills/month per adult male leopard, which is higher than reported by most previous studies. The leopards varied considerably in the time they spent outside the national park; only 1 individual appeared to subsist mainly by raiding livestock. The availability of medium-sized ungulates at adequate densities is likely to be important for future leopard conservation efforts. The management of problem individuals also may promote coexistence of humans and leopards, even in prey-rich areas.